2021
DOI: 10.1126/scitranslmed.abb6576
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils attenuate hepatic ischemia-reperfusion injury in mice through ST2-dependent IL-13 production

Abstract: Eosinophils are a myeloid cell subpopulation that mediates type 2 T helper cell immune responses. Unexpectedly, we identified a rapid accumulation of eosinophils in 22 human liver grafts after hepatic transplantation. In contrast, no eosinophils were detectable in healthy liver tissues before transplantation. Studies with two genetic mouse models of eosinophil deficiency and a mouse model of antibody-mediated eosinophil depletion revealed exacerbated liver injury after hepatic ischemia and reperfusion. Adoptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 54 publications
0
52
0
Order By: Relevance
“…Thus, under baseline conditions, eosinophils rapidly enter several tissues, mainly the gastrointestinal tract, adipose tissue, thymus, uterus, and mammary glands, where they promote a variety of essential homeostatic functions, such as immunoregulation, tissue repair, glucose homeostasis, protection against obesity, regulation of mammary gland development, and preparation of the uterus for pregnancy (reviewed in [ 1 ]). Moreover, eosinophils promote antitumor effects in colorectal cancer [ 2 , 3 , 4 ], hepatoprotective activities [ 5 ], and cardiac protection after myocardial infarction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, under baseline conditions, eosinophils rapidly enter several tissues, mainly the gastrointestinal tract, adipose tissue, thymus, uterus, and mammary glands, where they promote a variety of essential homeostatic functions, such as immunoregulation, tissue repair, glucose homeostasis, protection against obesity, regulation of mammary gland development, and preparation of the uterus for pregnancy (reviewed in [ 1 ]). Moreover, eosinophils promote antitumor effects in colorectal cancer [ 2 , 3 , 4 ], hepatoprotective activities [ 5 ], and cardiac protection after myocardial infarction [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, using a high-throughput evaluation of human primary tumors, Grisaru-Tal et al identified differential infiltration of eosinophils in anatomically distinct tumors, with high eosinophil counts in mucosal barrier organs such as the colon or esophagus [13]. Eosinophils additionally show hepatoprotective activity [14] and cardiac protective function after myocardial infarction [15]. Of particular interest, a robust inverse correlation between eosinophil numbers and severity of novel coronavirus disease of 2019 (COVID- 19) infection was observed [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…An important function of eosinophils is their antitumor effect in colorectal cancer [ 246 ]. Eosinophils show hepatoprotective activity [ 247 ] and cardiac protective function after myocardial infarction [ 248 ]. Of particular interest, a robust inverse correlation between eosinophil numbers and coronavirus disease 2019 (COVID-19) infection severity was observed most recently [ 249 ].…”
Section: Immunomodulatory Functions Of Hdlmentioning
confidence: 99%